The electrophoresis of histones in polyacrylamide gel and their quantitative determination - Johns, E. W. (1967)
1. A new method has been devised for the separation of the histone fractions of calf thymus by electrophoresis in polyacrylamide gel at pH2·4. 2. The fractions have been characterized by their relative mobilities with respect to a marker protein, bovine plasma albumin. 3. A method has been developed for the quantitative determination of the separated histone fractions by measuring the colour yields of dye–histone complexes formed in the gel.